Inhibitory Effects of Linear Lipopeptides From a Marine Bacillus subtilis on the Wheat Blast Fungus Magnaporthe oryzae Triticum - Chakraborty, Moutoshi; Mahmud, Nur Uddin; Gupta, Dipali Rani; Tareq, Fakir Shahidullah; Shin, Hee Jae; Islam, Tofazzal (Frontiers in Microbiology, 2020)
Wheat blast is a devastating fungal disease caused by a filamentous fungus, Magnaporthe oryzae Triticum (MoT) pathotype, which poses serious threat to food security of South America and South Asia. In the course of screening novel bioactive secondary metabolites, we found that some secondary metabolites from a marine Bacillus subtilis strain 109GGC020 remarkably inhibited the growth of M. oryzae Triticum in vitro at 20 µg/disk. We tested a number of natural compounds derived from microorganisms and plants and found that five recently discovered linear non-cytotoxic lipopeptides, gageopeptides A-D (1-4) and gageotetrin B (5) from the strain 109GGC020 inhibited the growth of MoT mycelia in a dose-dependent manner. Among the 5 compounds studied, gageotetrin B (5) displayed the highest mycelial growth inhibition of MoT followed by gageopeptide C (3), gageopeptide D (4), gageopeptide A (1) and gageopeptide B (2) with minimum inhibitory concentrations (MICs) of 1.5, 2.5, 2.5, 10.0 and 10.0 µg/disk, respectively. Application of these natural compounds also completely blocked formation of conidia in the MoT fungal mycelia in the agar medium. Further bioassay revealed that these compounds (1-5) inhibited the germination of MoT conidia and if germinated, induced deformation of germ tube and/or abnormal appressoria. Interestingly, application of these linear lipopeptides (1-5) remarkably suppressed wheat blast disease on detached wheat leaves. This is the first report of the inhibition of mycelial growth, conidiogenesis, conidial germination, appressoria formation and suppression of wheat blast disease by linear lipopeptides from the strain of B. subtilis. A further study is needed to evaluate the mode of action of these natural compounds for considering them as biopesticides for managing this notorious cereal killer.